If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = -2(3) + -5 Multiply f * x fx = -2(3) + -5 Multiply -2 * 3 fx = -6 + -5 Combine like terms: -6 + -5 = -11 fx = -11 Solving fx = -11 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -11x-1 Simplifying f = -11x-1
| (3x-6)(2x-2)=0 | | 1/4+2x=1/5x+1 | | 75=5+3x | | (x+2)*(x+1)+(x+3)*(x+1)=2x^2+12 | | .3x+1=13 | | 8x-2x+62=-8x+40 | | .5t+4=1 | | 3x+6(x+15)=162 | | 7x+3(2x+4)=116 | | 12.79+.11h=13.54-.07h | | 28-(2c+3)=2(2+5)+c | | .5(x+5)=7.5 | | 7x+5(x-7)=97 | | -10(x-24)=130 | | 2x+24=0.28571428571x | | 10(x+3)+9x+4=x_5+3 | | -10y=130 | | x-24=-13 | | 17-20q=(18-5q)4 | | -9(x-6)=-54 | | -12=12 | | 4x+4(5x-5)=196 | | 5/2x+1/2x=271/2+7/2x | | 12(x+13)=-48 | | 15(x-17)=-60 | | 6x+4(3x-18)=144 | | 15y=-60 | | z/2+7=8-z/2 | | x-17=-4 | | 6x+4x-57=38-9x | | 3+1/7x=6 | | 3(x-6)+2=5x-6 |